Growing up with Robots - Costa, Manuel F. M. (2008)
Piaget’stheoryofcognitivedevelopment[1] isconsideredafundamentalpedagogicaltoolthat indifferentapproaches,educatorsatdifferent levelsandsituationwidelyuse.Thevastmajorityofstudentshavetendency tolearninaconcretemannerbyexperiencingor feeling,andprocesstheinformationactivelyby experimentingdoingoractingupon[2].Hands-onexperimentalactivitieshavelong timeprovedtobeoneofthemosteffectiveways todrivethestudentstoasuccessfullearningof scienceandtechnology[3].Constructivismisapedagogicalapproach whereinastructuredwaythelearningprocessis centredintheprocessofbuildingorconstructing something.